Reconstruction, Replication and Re-Enactment in the Humanities and Social Sciences - Dupré, Sven; Harris, Anna; Kursell, Julia; Lulof, Patricia; Stols-Witlox, Maartje (Taylor & Francis Group, 2020)
This book offers sustained, interdisciplinary reflections on performative methods, variously known as Reconstruction, Replication and Re-enactment (RRR) practices across the fields of history of science, archaeology, art history, conservation, musicology and anthropology.